3D-NuS: A Web Server for Automated Modeling and Visualization of Non-Canonical 3-Dimensional Nucleic Acid Structures. Issue 16 (4th August 2017) - Patro, L. Ponoop Prasad; Kumar, Abhishek; Kolimi, Narendar; Rathinavelan, Thenmalarchelvi
Abstract: The inherent conformational flexibility of nucleic acids facilitates the formation of a range of conformations such as duplex, triplex, quadruplex, etc . that play crucial roles in biological processes. Elucidation of the influence of non-canonical base pair mismatches on DNA/RNA structures at different sequence contexts to understand the mismatch repair, misregulation of alternative splicing mechanisms and the sequence-dependent effect of RNA–DNA hybrid in relevance to antisense strategy demand their three-dimensional structural information. Furthermore, structural insights about nucleic acid triplexes, which are generally not tractable to structure determination by X-ray crystallography or NMR techniques, are essential to establish their biological function(s). A web server, namely 3D-NuS (http://iith.ac.in/3dnus/ ), has been developed to generate energy-minimized models of 80 different types of triplexes, 64 types of G-quadruplexes, left-handed Z-DNA/RNA duplexes, and RNA–DNA hybrid duplex along with inter- and intramolecular DNA or RNA duplexes comprising a variety of mismatches and their chimeric forms for any user-defined sequence and length. It also generates an ensemble of conformations corresponding to the modeled structure. These structures may serve as good starting models for docking proteins and small molecules with nucleic acids, NMR structure determination, cryo-electron microscope modeling, DNA/RNA nanotechnology applications and molecular dynamics simulation studies. Graphical Abstract: Highlights: Web Server for automated modeling and visualization of nucleic acid structures DNA/RNA duplexes containing eight different mismatches of any sequence context and length can be generated. There are 80 different triplexes and 64 different quadruplexes of desired combinations of DNA and RNA strands that can be modeled. Ensemble of conformations can also be generated.